2013
DOI: 10.1371/journal.pone.0079993
|View full text |Cite
|
Sign up to set email alerts
|

Association between Telomere Length and Type 2 Diabetes Mellitus: A Meta-Analysis

Abstract: BackgroundSeveral epidemiological studies have examined the association between shortened telomere length and type 2 diabetes mellitus (T2DM), while the results remained conflicting. We conducted a meta-analysis to derive a more precise estimation of the relationship between them.MethodsWe systematically reviewed the databases of PubMed, EMBASE, and Web of Science for all studies on the association between telomere length and T2DM. We conducted this study assessed by STATA 11.0. Data were summarized using rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
154
3
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(167 citation statements)
references
References 32 publications
3
154
3
7
Order By: Relevance
“…The associations between telomeres, diseases, physiological aging, and decline in physical functioning are ambiguous. Telomere length has shown a modest association with several risk factors (Haycock et al 2014;Willeit et al 2014) and various chronic diseases (Zhao et al 2013;Haycock et al 2014;Albrecht et al 2014). Shortened telomeres can result in cell cycle arrest, tumor suppression, and loss of functional tissue via senescence or apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The associations between telomeres, diseases, physiological aging, and decline in physical functioning are ambiguous. Telomere length has shown a modest association with several risk factors (Haycock et al 2014;Willeit et al 2014) and various chronic diseases (Zhao et al 2013;Haycock et al 2014;Albrecht et al 2014). Shortened telomeres can result in cell cycle arrest, tumor suppression, and loss of functional tissue via senescence or apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have already shown that LTL is inversely associated with mortality (Cawthon et al 2003) and several age-related diseases such as cardiovascular diseases, COPD, cancer, and type 2 diabetes (Zhao et al 2013;Haycock et al 2014;Albrecht et al 2014). The evidence on the association between LTL and physical functioning is inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Así pues, estos factores son los que están implicados con enfermedades de muy diferente espectro que están relacionadas con los telómeros (48)(49)(50). Entre estas enfermedades están las ligadas al envejecimiento: enfermedades de tipo cardiovascular (infarto de miocardio, enfermedad cerebrovascular, enfermedad arterial periférica) (27,36), cirrosis hepática, hipertensión, aterosclerosis, diabetes, cáncer y enfermedades neurodegenerativas (alzhéimer, párkinson) (14,(51)(52)(53)(54). La longitud de los telómeros predice la mortalidad y las enfermedades relacionadas con el envejecimiento (49).…”
Section: Introductionunclassified
“…Some cells, such as germline cells, have greater ability to preserve telomere length through the enzymatic activity known as telomerase. Leukocyte telomere length (LTL) has been proposed to be a marker for biological aging, and shortened LTL has been related with higher allcause mortality (Honig et al 2012) as well as a variety of age-related conditions such as cardiovascular disease (Estruch et al 2013;Mainous et al 2010;Perez-Rivera et al 2014), diabetes (Zhao et al 2013), and dementia (Honig et al 2012).…”
Section: Introductionmentioning
confidence: 99%